CHICKPEA (SICER ARIETINUM L) YIELD DEPENDING ON NUTRIENTS IN THE CONDITIONS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Lykhochvor , В.; Vynnytskyi , В.; Pushchak , В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Research on the impact of various fertilizer elements on the yield of the Yaryna variety chickpea was conducted from 2022 to 2024. A total of 10 fertilizer options were tested according to the following scheme: N0Р0К0 (control), P20К30, P40К60, N30Р40К60, N30Р40К60S20, N30Р40К60S20Mg20, N30Р40К60S20Mg20 + mono Boron, N30Р40К60S20Mg20 + mono molybdenum, N30Р40К60S20Mg20 + mono cobalt, N30Р40К60S20Mg20 + B, Mo, Co. The chickpeas were grown following winter wheat, with a seeding rate of 0.7 million seeds per hectare. Sowing occurred between April 1 and 3, and the seeds were treated with Vitavax 200FF at a rate of 3 liters per ton. The herbicide Racer, k.e. (2.5 l/ha) was applied for weed control, while the insecticide Fastak, k.e. was used at a rate of 0.15 l/ha to manage pests. To protect against diseases, fungicides were applied three times, as disease damage can be significant in conditions with ample moisture. The fungicide Rex Duo, k.s. (0.5 l/ha) was applied during the budding phase, Abacus mk (1.5 l/ha) during flowering, and Folicur 250 EW (1.0 l/ha) during the grain filling phase. The lowest chickpea grain yield was recorded in the control group without fertilizers, at 1.74 t/ha. With the application of P20K30, the yield increased to 2.02 t/ha, an increase of 0.28 t/ha. When the phosphorus and potassium fertilizer rate was doubled to P40K60, the yield rose to 2.24 t/ha. Adding 30 kg of nitrogen (N30) to the P40K60 base increased the yield further to 2.44 t/ha. Incorporating sulfur in the fertilization system raised the yield to 2.58 t/ha, and adding magnesium increased it to 2.72 t/ha. Among the microelements applied foliar during the growing season, boron was expected to have the most significant effect on chickpea productivity, boosting the yield to 2.84 t/ha. However, the increases from molybdenum and cobalt were smaller, resulting in lower yields compared to the boron treatments. In the Western Forest-Steppe of Ukraine, the highest chickpea grain yield of the Yaryna variety was 2.98 t/ha, achieved by following the fertilization system N30Р40К60S20Mg20 + В, Мо, Со, which is 1.24 t/ha, or 71.3%, higher than the control without fertilizers. The greatest yield increases were observed with the application of Р20К30 (0.28 t/ha) and the combined use of the three microelements during the growing season - B+Mo+Co (0.26 t/ha).